White Matter Integrity in Obstructive Sleep Apnea before and after Treatment. Issue 9 (1st September 2014) - Castronovo, Vincenza; Scifo, Paola; Castellano, Antonella; Aloia, Mark S.; Iadanza, Antonella; Marelli, Sara; Cappa, Stefano F.; Strambi, Luigi Ferini; Falini, Andrea
Abstract: Study Objectives: Obstructive sleep apnea (OSA) is commonly associated with cognitive and functional deficits, some of which are resolved after continuous positive airway pressure (CPAP) treatment. The investigation of brain structural changes before and after treatment could provide deep insights into the pathogenesis and the reversibility of this disorder. We hypothesized that severe OSA patients would have altered white matter (WM) integrity and cognition and that treatment would improve both the structural damage and the cognitive impairment. Design: Prospective clinical study. Setting: The Sleep Disorders Center and the Center of Excellence in High-Field Magnetic Resonance Imaging at Vita-Salute San Raffaele University, Milan, Italy. Participants: Seventeen never-treated consecutive OSA patients were evaluated before and after treatment (after 3 and 12 months) and compared to 15 matched healthy controls. Intervention: CPAP. Measurements: WM integrity measured by diffusion tensor imaging (DTI) and cognitive performance (measured with neuropsychological testing) before and after 3 and 12 months of CPAP. Results: Results in pre-treatment OSA patients showed impairments in most cognitive areas, mood and sleepiness that were associated with diffuse reduction of WM fiber integrity reflected by diminished fractional anisotropy (FA) and mean diffusivity (MD) in multiple brain areas. After 3 months of CPAP, only limited changes of WM were found. However, over the course of 12 months CPAP treatment, an almost complete reversal of WM abnormalities in all the affected regions was observed in patients who were compliant with treatment. Significant improvements involving memory, attention, and executive-functioning paralleled WM changes after treatment. Conclusions: Changes of WM DTI "signatures" of brain pathology in OSA patients are appreciable over the course of 12-month treatment with CPAP in most of the regions involved. Recovery of cognitive deficits after treatment is consistent with the presence of a reversible structural neural injury in OSA in patients who were compliant with treatment.